1995
DOI: 10.1101/gad.9.6.686
|View full text |Cite
|
Sign up to set email alerts
|

twist is required in head mesenchyme for cranial neural tube morphogenesis.

Abstract: To understand the role of twist during mammalian development, we generated twist-null mice. twist-null embryos died at embryonic day 11.5. Their most prominent phenotype was a failure of the cranial neural folds to fuse. Mutant embryos also had defects in head mesenchyme, somites, and limb buds. Chimera analysis suggested that head mesenchyme was required for cranial neural tube closure and that twist acted in a cell-autonomous manner in this tissue. In addition, in the head mesenchyme region of chimeras, twis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
480
2
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(507 citation statements)
references
References 40 publications
20
480
2
5
Order By: Relevance
“…20 TWIST1 upregulation, however, has mainly been correlated with aggressive phenotypes, metastasis formation and poor prognosis. 3 TWIST1 is required for cell migration during both development 21 and oncogenesis. 22 Thus, TWIST1 downregulation might help primary tumor cells to remain localized early in breast cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…20 TWIST1 upregulation, however, has mainly been correlated with aggressive phenotypes, metastasis formation and poor prognosis. 3 TWIST1 is required for cell migration during both development 21 and oncogenesis. 22 Thus, TWIST1 downregulation might help primary tumor cells to remain localized early in breast cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this hypothesis, it has been shown that in chimeric Sox9 Ϫ/Ϫ mice, mesenchymal cells deficient for SOX9 could not differentiate into chondrocytes (50). Mesenchymal cells in Twist knockout mice also display abnormalities in differentiation and proliferation, and overexpression of Twist in osteoblast-like cells inhibits their differentiation (77,78). It is likely that the combined down-regulation of SOX9 and up-regulation of TWIST in dedifferentiated cells is prohibitive for redifferentiation.…”
Section: Discussionmentioning
confidence: 97%
“…Both reduced and increased numbers of head (Chen and Behringer, 1995;Zhao et al, 1996). Twist is expressed in head mesenchyme cells, and Twist knockout mice exhibit exencephaly (Chen and Behringer, 1995;Soo et al, 2002).…”
Section: Neural Patterning In Gcn5 Flox(neo)/⌬ Mutantsmentioning
confidence: 99%
“…Whole mount RNA in situ hybridization was performed as described (Nagy et al, 2003). The Twist, Ptc1, and Gli1 probes were kindly provided by Dr. R. Behringer (Chen and Behringer, 1995;Soo et al, 2002). Probes for Cart1 and Sox9 were kindly provided by Dr. B. de Crombrugghe (Dept.…”
Section: In Situ Hybridizationsmentioning
confidence: 99%